군산시 중년여성의 체지방률에 의한 비만도 분류에 따른 영양소 섭취와 혈중지질에 관한 연구 - 장혜순(Hye Soon Chang) (Korean journal of community nutrition, 2010)
The purpose of this study was to compare nutrient intakes and blood lipids of middle-aged women according to the obesity index by %Fat. Subjects were assigned to one of the following groups based on percentage of body fat (%Fat): normal weight (18% ~ < 28%), overweight (28% ~ < 33%) and obesity (over 33%). Nutrient intakes were evaluated based on questionnaires of 24 hours recall method and blood lipids were analyzed by blood analyzer. The results were as follows. 1) Nutrient intakes were that carbohydrates and fat intakes in obesity group were higher than normal and overweight group but the difference was not significant, and protein intake rate was similar all groups. The intake rate of calcium was higher in normal group than obesity group (p < 0.05), and obesity group ingested under dietary reference intakes. The intake rate of iron was higher in obesity group than normal group (p < 0.05). 2) TG, TC, VLDL and TC/HDL in obesity group were higher than normal group (p < 0.001). The attack rate of coronary heart disease in obesity group is higher than normal group (p < 0.01), LDL, blood glucose and blood pressure in obesity group were higher than normal group (p < 0.01), and HDL was a little higher in normal group than obesity group, but the difference was not significant. 3) The correlation of anthropometric measurements, blood glucose, blood lipid, and blood pressure had significant results. Weight was associated positive level with blood glucose, blood lipid and blood pressure. Waist and WHR were associated positive level with blood glucose and blood lipid but weren't associated with blood pressure. BMI was associated positive level with blood glucose, blood lipid and blood pressure, %Fat was associated positive level with blood lipid and blood pressure, but wasn't associated with blood glucose. These results suggest that the decrease of waist on blood glucose control is better than decrease of % Fat and BMI, the decrease of %Fat and BMI on blood pressure control is better than decrease of waist, and the decrease of %Fat on blood lipid control is better than waist and BMI. The nutritional education for obesity treatment must perform to analyze the blood and assess the obesity degree by %Fat, waist and BMI before nutritional education, so the obesity treatment will be effectively.